Strategi Promosi Dalam Mengembangkan Bisnis Transportasi Pada Perusahaan Transportasi Blue Bird Jakarta - Karlina; Sosi Marlia Nggadas (Jurnal Sains Terapan Pariwisata, 2016)
Blue bird is taxi Company that has been dabbling in the world business of transporting many years and being firm taxi number one in Indonesia. Become the brand image make blue bird one step in front of all their competitor .Blue bird also has information systems that sophisticated, so that it could make a firm keeps create new innovation’s. And has succeeded to grab the attention of public.Blue Bird does some marketing in order to maintain and increase the customer, This Company always full of computation. Blue bird can see the potential business growth and able to take potential business properly. This company is very observant to see business opportunities from year to year . For example from the sector of tourism industry, with many tourists both local and international, Make blue bird continue to provide transportation for comfortable and worthy of the holiday lovers. Not only in jakarta, Blue bird also operating in several other large cities. Blue bird is very proud and grateful because it can contribute to this nation. Need a long time and long struggle to establish the company with good image and quite well-respected in this country Need a long time and long struggle to establish the company with good image and quite well-respected in this country. Not only contributed in the sector of transportation but also in terms of absorption of labor in order to fulfill the demand that is increasing from year to year. All employees and the drivers was recruited in a process that is very tight so as to be firm obtain employees and drivers who competent and better, as well as responsible each other. The company blue bird is the best taxi company Indonesia, so get the brand image that both the community in Indonesia. But the blue bird must continue to improve the quality, because the more competitors, which will be a threat, so that the company still be the best taxi company, who continue to grow and contribute to this Country.